A MODEL FOR TURNOVER INTENTION: BANKING INDUSTRY IN MALAYSIA - Mohammad Falahat; Gee Siew Kit; Liew Chin Min (Asian Academy of Management Journal, 2019)
The issue of staff’s intention to leave is a huge concern for senior management and human resource managers. It is one of the costliest and most challenging issues within any organisation worldwide. The banking industry records the highest turnover rate in Malaysia. High employee turnover has a profound influence on the banks’ performance and productivity. The primary purpose of this research is to explore the real causes of turnover intention in the banking industry in Malaysia. The result from a total of 395 respondents showed that working environment, job enrichment, and job stress could significantly affect job satisfaction; whereas job stress and job satisfaction will substantially affect turnover intention. The results also found that working environment and job stress have an indirect effect on turnover intention.